2014
DOI: 10.1177/0009922814528037
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of Home Oxygen Therapy to Very Low Birth Weight Infants in Germany

Abstract: Management of pediatric home oxygen therapy is diverse in Germany. Optimal SpO2 targets have to be further investigated by controlled studies and German guidelines should be established. Until then practice should abide by existing foreign guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the present study, the rate of home oxygen use ranged from 2.9% to 36.4% in 29 NICUs as well as even 0% in 14 NICUs. A German study reported that NICUs admitting > 50 VLBWIs annually significantly and more frequently prescribed home oxygen and aimed for SpO 2 levels closer to the physiological range than those admitting fewer VLBWIs (19). However, in the present study, we could not find any correlation for NICU size and prescription rate of home oxygen at discharge in the VLBWIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rate of home oxygen use ranged from 2.9% to 36.4% in 29 NICUs as well as even 0% in 14 NICUs. A German study reported that NICUs admitting > 50 VLBWIs annually significantly and more frequently prescribed home oxygen and aimed for SpO 2 levels closer to the physiological range than those admitting fewer VLBWIs (19). However, in the present study, we could not find any correlation for NICU size and prescription rate of home oxygen at discharge in the VLBWIs.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing care, therefore, implies understanding the characteristics and physiology of NB, knowledge of the functioning of the respiratory system and the capacity to intervene at the appropriate time. 13,18 Regarding the nursing care to NB undergoing oxygen therapy, it was possible to observe the following lines: It was possible to notice that the interviewed nurses mentioned the use of oxygen therapy techniques, heating, humidification, hygiene of the system and the device, and physical examination for neonatal care. However, the few references to hand hygiene and recordkeeping as a form of care are noteworthy, even though these are essential and basic behaviors in assisting all individuals to prevent complications and control their clinical evolution.…”
Section: Nursing Care Towards the Newborn Undergoing Oxygen Therapymentioning
confidence: 99%
“…Nursing care, therefore, implies understanding the characteristics and physiology of NB, knowledge of the functioning of the respiratory system and the capacity to intervene at the appropriate time. 13,18 Regarding the nursing care to NB undergoing oxygen therapy, it was possible to observe the following lines:…”
Section: Nursing Care Towards the Newborn Undergoing Oxygen Therapymentioning
confidence: 99%